Review of Alzheimer’s Disease Classification Techniques - Yew, Aow Yong Li; Sulong, Ghazali (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Alzheimer’s disease is a brain degeneration illness. It requires earlier detection in order to improve the quality of life of the patient. Many researchers have studied different computed aided approaches in order to help in the diagnosis of the disease. However, there are few well-known techniques that were used in most of the studies. It is challenging in mild cognitive impairment classification too. Therefore, this paper will review the common used methods and the state-of-art methods in Alzheimer’s disease classification. This helps researchers to identify the suitable methodologies in different stages of classification.